The Meaning Of True Happiness Of John Tyree Reflected In Nicholas Sparks "Dear John" (2006): An Individual Psychological Approach - Asih, Yuli Retno, Titis Setyabudi, S.S, M.Hum (2017)
The major problem of this research is how John Tyree finds the meaning of true happiness in Dear John novel by Nicholas Sparks. The researcher uses an individual psychological approach by Alfred Adler. The objectives of the study are: 1) to describe how John Tyree find the meningof true happiness in Dear John novel, 2) to to describe the problems affecting the psychology of John Tyree in Dear John novel, and 3) to explain the definition of true happiness in Dear John novel. The researcher uses qualitative method. The researcher uses two data sources, namely: primary and secondary. The primary data source is Dear John novel by Nicholas Sparks. Then, the secondary data source is from websites, articles, biography of the author and some books that support the research. The technique of analyzing data is descriptive qualitative. Based on the analysis, the researcher found the meaning of true happiness by John Tyree in Dear John novel. The researcher concluded that the real happiness is giving priority to the happiness of those we love before our happiness, and willing to accept the risk of any kind has become our choices. Keyword: happiness, an individual psychological theory, dear john, Nicholas Sparks